2011
DOI: 10.3345/kjp.2011.54.7.304
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of drug provocation tests in children with a history of adverse drug reaction

Abstract: PurposeThere are very few reports of adverse drug reactions (ADR) and almost no study of drug provocation test (DPT) in Korean children. We aimed to assess the role of DPT in children with unpredictable ADRs, and compare the causative drugs and clinical characteristics between detailed history of ADRs and result of DPTs.MethodsWe included 16 children who were experienced ADRs referred to pediatric allergy clinic at Ajou University Hospital (January 2006 to December 2009). With various suspected drugs, 71 DPTs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
2
12
0
1
Order By: Relevance
“…23,24 A previous Korean study also reported a lower positive rate of 23.9% (17/71 cases) compared to that of our study. 15 We postulated that the number of patients included in this study and the background factors of study subjects were the cause of differences in the prevalence of positive DPT findings.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…23,24 A previous Korean study also reported a lower positive rate of 23.9% (17/71 cases) compared to that of our study. 15 We postulated that the number of patients included in this study and the background factors of study subjects were the cause of differences in the prevalence of positive DPT findings.…”
Section: Discussionmentioning
confidence: 98%
“…8 However, there is a scarcity of data with respect to DPTs in Korean children. 7,15 Thus, we analyzed all of the DPTs performed in our pediatric allergy clinic over the course of 20 years. Importantly, this is the largest and most extensive pediatric DPT study conducted in Korea to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3033) According to domestic reports, drug provo cation tests (DPT) could be safely performed in pediatric pa tients with higher diagnostic accuracy. 34,35) Crossreactivity between betalactam antibiotics is due to the side chain R1 in amoxicillin, ampicillin, and cefaclor, which have identical or almost identical side chains, have been shown to have crossreacti vity by skin test ing; and in ceftriaxone and cefotaxime, which have identical side chains and also show skin test crossreacti vity. It is recommended that we evaluate medication side chains to safely challenge beta lactams with different side chains.…”
Section: Beta-lactam Antibioticsmentioning
confidence: 99%